GAMBARAN POLA ASUH ORANG TUA DI MASA PANDEMI COVID-19 PADA ANAK USIA SEKOLAH - Novia Rizana; Trisna Sari; Rauzatul Uli (Sekolah Tinggi Ilmu Kesehatan Muhammadiyah Lhokseumawe, 2022)
The Covid-19 pandemic situation has changed everything. Nowadays, the role of parents is really the main thing in creating the happiness and success of a child. Various forms of parenting will certainly have implications for the formation of children's character. The purpose of the study was to find out how the description of parenting patterns during the Covid-19 pandemic for school-age children.This research design uses descriptive research method. The population in this study were all parents who have children aged 6-18 years as many as 64 children. The number of samples in this study was 64 using total sampling technique. This research was carried out on July 01 to August 07, 2021. The analysis was carried out using a computerized process through univariate analysis.Based on the results of the study, it was found that the parenting pattern of parents during the Covid-19 pandemic for school-age children in Gampong Kambam, Muara Batu District, North Aceh Regency, was more good by 44 respondents (68.8%), compared to 20 respondents (31.3%).Based on the results of the study, it can be concluded that parenting patterns during the Covid-19 pandemic for school-age children are in the good category. It is hoped that parents can provide positive parenting patterns so that school-age children avoid the Covid-19 pandemic. Because parents have full responsibility in meeting the needs of children.